Comparative analysis of Kenguri sheep farmers market orientation under intensive and extensive rearing system in Yadgir district of Karnataka - Kanakaraja, M G; Sagar , M; Kiran, Jettaboina Sai; Jeevan , Kumar K S (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
In the present study total of 20 intensive Kenguri sheep farmers having the herd size ranging from (35 to 300) and 20 extensive Kenguri sheep farmers having the herd size ranging from (25 to 1480) of Yadgir district of Karnataka were selected based on the availability and the sheep market orientation criteria were analyzed. The most farmers were dependent on body conformation (45.00%) followed by body weight (wt.) (40.00%) and age (15.00%) in intensive system for price fixation. In extensive system, price fixing was equally dependent on age as well as body conformation (40.00%) followed by few were using body wt. (20.00%). Market availability (90.00% and 75.00%), market plan information (80.00% and 50.00%), market price information (60.00% and 45.00%) and satisfaction about market (65.00% and 40.00%) were having major and minor roles in intensive and extensive systems respectively. The average (avg.) market age of sheep (7.43 ± 0.26) months in intensive system was more compared to extensive system (4.60 ± 0.19) months. The mean body wt. at sale in intensive system (33.93 ± 1.13) kgs was more compared to extensive system (20.00 ± 1.69) kgs. The avg. selling price per culled adult in intensive system (₹9059 ± 41.75) was more compared to extensive system (₹7998 ± 49.98). In intensive system (₹11247 ± 30.32) was the avg. selling price per excess stock which was more paralleled to extensive system (₹11099 ± 31.15). The avg. selling price per marketable stock in intensive system (₹313 ± 9.86) was less compared to extensive system (₹427 ± 12.89).